Analytical method for detecting sulfated oligosaccharides - CHIANG, YUNG-TE; HUANG, I-MIN; WU, CHIA-YEN; WANG, CHUNG-YAO; CHAO, HELEN (2015)
The present invention describes an analytical method for detecting and quantitating poly-sulfated oligosaccharides, including Fondaparinux sodium, using hydrophilic interaction ultra-performance liquid chromatography (HILIC-UPLC) coupled with a charged aerosol detector (CAD) or a mass spectrometer (MS). This analytical method provides in-process control in a total synthesis of highly sulfated oligosaccharides by separation, quantification and mass identification. Systems and conditions utilizing such methods are also provided.